1980
DOI: 10.1051/rnd:19800108
|View full text |Cite
|
Sign up to set email alerts
|

L'organe pinéal du Brochet (Esox lucius, L.). IV. Sérotonine endogène et activité monoamine oxydasique ; étude histochimique, ultracytochimique et pharmacologique

Abstract: Summary. The pineal organ of the pike (Esox lucius L.). IV. Endogenous serotonin and monoamine oxidase activity : An histochemical, ultracytochemical and pharmacological studyThe pineal organ of the pike was studied in natural conditions in autumn and winter (short days). Using fluorescence histochemistry and drug treatments, the agranular pool of 5-HTP/5-HT (5-hydroxytryptophan and/or 5-hydroxytryptamine), the melatonin precursor, was found in different receptor line cells (Falcon, 1979b). This result confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
(9 reference statements)
0
11
0
3
Order By: Relevance
“…Direct identification of melatonin by immunocytochemistry has been questioned on methodological grounds (Ekströ m & Meissl 1997). The presence of indoleamines has usually been demonstrated by biochemical and autoradiographic methods (Meiniel et al 1972;Collin et al 1982;Falcon & Collin 1985;Meiniel 1987), formaldehyde-induced fluorescence (Collin 1968a;Ueck 1973;Juillard et al 1977;Meiniel 1978;Falcó n et al 1980 Oksche (1983); cf. figures 6 and 7) in the vertebrate groups discussed in this paper.…”
Section: Are There Really Many Types Of Pineal Photoreceptors?mentioning
confidence: 99%
“…Direct identification of melatonin by immunocytochemistry has been questioned on methodological grounds (Ekströ m & Meissl 1997). The presence of indoleamines has usually been demonstrated by biochemical and autoradiographic methods (Meiniel et al 1972;Collin et al 1982;Falcon & Collin 1985;Meiniel 1987), formaldehyde-induced fluorescence (Collin 1968a;Ueck 1973;Juillard et al 1977;Meiniel 1978;Falcó n et al 1980 Oksche (1983); cf. figures 6 and 7) in the vertebrate groups discussed in this paper.…”
Section: Are There Really Many Types Of Pineal Photoreceptors?mentioning
confidence: 99%
“…Les réactions radioautographiques (séries 10-15, 18-29) sont régulièrement présentes dans les CTP et les CIE, toujours plus intenses dans la première catégorie cellulaire que dans la seconde. L'incorporation in vivo (série 10-15) et in vitro (série 18-29) de 5-HTP-3 H a eu lieu en période diurne, c'est-à-dire dans les conditions où le taux de 5-HT endogène est maximum chez de nombreuses espèces, y compris chez le Brochet (Falcon et al, 1980). De plus, compte tenu de nos conditions expérimentales, des données de !/Vilhoft et Quay (1965) et de celles de la série 1-3, il est raisonnable de concevoir que la décarboxylation (Falcon et al, 1980) du 5-HTP-3 H conduise à la formation de 5-HT-3 H, dans l'organe pinéal de Brochet.…”
unclassified
“…L'incorporation in vivo (série 10-15) et in vitro (série 18-29) de 5-HTP-3 H a eu lieu en période diurne, c'est-à-dire dans les conditions où le taux de 5-HT endogène est maximum chez de nombreuses espèces, y compris chez le Brochet (Falcon et al, 1980). De plus, compte tenu de nos conditions expérimentales, des données de !/Vilhoft et Quay (1965) et de celles de la série 1-3, il est raisonnable de concevoir que la décarboxylation (Falcon et al, 1980) du 5-HTP-3 H conduise à la formation de 5-HT-3 H, dans l'organe pinéal de Brochet. Les résultats obtenus après inhibition expérimentale de la désamination oxydative (série 1-3), suggèrent l'existence d'une surcharge anormale de 5-HT-3 H (après 3 h) dans les CTP et les CIE et, en conséquence, une dégradation importante de la 5-HT, dans les conditions normales.…”
unclassified
See 1 more Smart Citation
“…Histochemical, immunocytochemical, and biochemical studies have demonstrated that pineal cells in these species contain the indoles, 5-hydroxytryptophan, 5-hydroxytryptamine (serotonin) and melatonin (Falcon et al, 1980(Falcon et al, , 1981Fenwick, 1970 b ;Hafeez and Zerihun, 1976 ;Meissl et al, 1978 ;Owman and Rudeberg, 1970 ;Vivien-Roels et al, 19811 Quay, 1970 ;Weber, 1974, 1976). Levels of these compounds and protein content fluctuate over daily light : dark cycles (Birks and Ewing, 1981 b ;Falcon et al, 1980 ;Meissl et al, 1978 ;Weber, 1974, 1976 (Fenwick, 1970 b), and the killifish (de Vlaming et al, 1974) ; the effects generally depending upon the time of year and photoperiod. On the basis of these observations, it would be important to determine the effects of various photoperiod-temperature regimes on circadian rhythms of indoles and their related enzymes.…”
Section: Introductionmentioning
confidence: 99%